PATTERN OF LIP PRINTS AMONG THE UNDERGRADUATE STUDENTS OF A TERTIARY CARE CENTRE IN SOUTH INDIA – AN OBSERVATIONAL STUDY - Rajesh, J James; Chander, U Jagdish Kamal; G, Manigandaraj; R, Janarthanan (Journal of Forensic Medicine and Toxicology, 2022)
Background: The wrinkles and grooves on the labialmucosa (called sulci labiorum) form a characteristic pattern which is known as lip print. The study of these lip print is called cheiloscopy. Lip prints are consideredunique to an individual and analogous to fingerprints. Aim & Objectives: -To observe the various lip printpatterns in the study population.- To estimate the prevalence of lip print pattern,quadrant wise.- To evaluate the gender differences in the lip print pattern. Materials & Methods: It’s an observational study,conducted among healthy male and female students of 18– 25 years of a tertiary care centre in South India. The sample size was 250. Lip prints of the students were taken by four different methods and were analysed with the magnifying hand lens. Results: The most common type of lip print was Type I, followed by Type III & Type II. On the grounds of gender,Type I was the most common in both Male & Female,followed by Type III. Expression of Type IV & V were more in males whereas expression of Type II was more in females. Conclusion: A lip print found at the scene of a crime could turn out to be a strong evidence material of the crime. Lip prints, as one of the dermatoglyphics, have been used asgenetic markers in many congenital and clinical diseases too.